2005
DOI: 10.1577/ft03-106.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Environmental Variability and Military Training on Stream Biota of Three Headwater Drainages in Western Louisiana

Abstract: We collected fishes and macroinvertebrates seasonally from eight headwater streams in three different drainage basins (the Red, Calcasieu, and Sabine rivers) crossing Peason Ridge Training Area in west-central Louisiana. Peason Ridge is part of the Fort Polk military training facility. We used multivariate analyses to test the effects of physical variables (i.e., current velocity, depth, and substrate), time (seasonal variability), drainage basin, and military training activities on assemblage structure. Tribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Thus, the spatial location of sites may have a stronger influence than the local environmental conditions. This pattern has been documented in other headwater systems (Williams et al 2002(Williams et al , 2005. In previous work, this has been because of the overriding influence of refugia areas during low water.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, the spatial location of sites may have a stronger influence than the local environmental conditions. This pattern has been documented in other headwater systems (Williams et al 2002(Williams et al , 2005. In previous work, this has been because of the overriding influence of refugia areas during low water.…”
Section: Discussionsupporting
confidence: 69%
“…Other studies have used similar multivariate techniques to test hypotheses about species-environment relationships at different spatial and temporal scales or the effects on aquatic assemblages (Anderson and Willis 2003;Angermeier and Winston 1998;Griffith et al 2001;McArdle and Anderson 2001;Nerbonne and Vondracek 2001;Wang et al 2003;Williams et al 2003Williams et al , 2005. First, correlation of the variables to each other and to IBI score was assessed to reduce redundancy in the data set.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and function of aquatic communities is influenced by factors operating across a range of spatial and temporal scales including geography, geology, climate, richness of regional species pools, stream order and network position, local stream habitat, water quality, and flow characteristics (Pusey et al 1995;Richards et al 1996;Allan et al 1997;Allan 2004;Angermeier and Winston 1998;Lammert and Allan 1999;Snyder et al 2003;King et al 2005;Williams et al 2005). Gangloff and Faminella (2007) found that relatively minor changes in channel gradient and bankfull depth may have large effects on mussel assemblages in Appalachian streams.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies concerning military disturbances and environmental effects on land (Wilson, 1988;Ayers, 1994;Lehman et al, 1999;Hirst et al, 2000;Whitecotton et al, 2000;Smith et al, 2002;Williams et al, 2005;Leis et al, 2005;Latham et al, 2007;Warren et al, 2007). These studies have used field experiments, observations, data monitoring and technical methods such as a Geographic Information System (GIS), computer simulation and multi-criteria analysis (Warren et al, 1989;Mendoza et al, 2002;Herl et al, 2005;Wang et al, 2008).…”
Section: Empirical Studies On Environmental Impacts Of Military Activmentioning
confidence: 99%